The estimation of Lymnaea rubiginosa and other freshwater snails populations in the rice fields and pond in Bogor, West Java - S Widjajanti (Indonesian Center for Animal Research and Development (ICARD), 1998)
The effect of feeding supplement and anthelmintic treatments on the establishment of parasites and the performances of lambs was studied in 24 St . Croix x Local Sumatra Crosses infected with Haemonchus contortus larvae (L3) . The study consisted of a 2 x 2 factorial arrangement involving two levels of supplement (1 .6% and 0.5% body weight ) and two levels of larval infection (0 and 3,000 L3 initial dose followed by a 1,000 L3-weekly dose) .The supplement x infection interaction was significant (P< 0.0001) on the egg counts and total serum proteins, but not on the PCV values (P>0.10) . The interaction was resulted from the shift in the magnitude of difference between supplement or between infection level and not by the shift in the rank between treatments . The 1 .6% body weight (BW) group had lower (P<0.0001) mean egg count than the 0.5% BW group (1,588 vs. 7,880) . Consistently, the blood PCV value and total serum proteins of lambs receiving 1 .6% BW supplement were higher (P<0.0001) than the 0.5% BW supplement group (28 .3 vs . 23 .8 and 5 .2 vs . 4.6, respectively) . Infection resulted in decreased feed and nitrogen (N) intake, but had no effect on fecal-N (P>0.0001). N-excretion (fecal-N + Urine-N) was not altered (P>0.10) by Haemonchus infection, but N-retention decreased in infected lambs due to a reduction in N intake . The effect of supplement and Haemonchus infection was significant (P<0.0001) on daily gain . Lambs on the 1 .6% BW supplement group grew faster than on the 0.5% BW supplement group whether they were infected or not . Infected lamb receiving 0.5% BW supplement lost weight during the experiment . It is concluded that an approach that combines the use of anthelmintics and supplement could ameliorate the influence of gastro-intestinal parasites on the performances of lambs, and reduces the intensity of using anthelmintics in controlling the parasites . Key words : Supplement, anthelmintics, Haemonchus contortus, lambs